BUNGA KECIL DI ASPAL KOTA MANADO: PERSPEKTIF PASTORAL KONSELING DALAM MEMBANGUN KESEJAHTERAAN EMOSIONAL DAN SPIRITUALITAS ANAK JALANAN - Tadung, Frieska Putrima; Salindeho, Veibe (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2024)
This research is a descriptive qualitative research that provides a description of the pastoral counselling as well as the collective expectations as a positive self-transformation catalyst focus to build the emotional and spiritual welfare of the streets. Street children facing the dynamics of life on the streets that require pastoral care and counseling in supporting and developing street children in terms of emotional and spiritual.